Constraints in Empowerment of Rural Women in District Kanpur Dehat - Awasthi, U.P. Nimisha; Sahu, Anjali; Singh, A.K.; Tripathi, M.N. (Indian Journal of Extension Education, 2020)
Empowerment is a multi-faceted, multi-dimensional and multilayered concept. With regards to women, empowerment is a process in which women gain greater share of control over resources- material, human and intellectual like knowledge, information, and ideas and financial like money- and control over decision making in the home and community. Rural women still do not have ownership on land and the pattas are allotted in the name of their husband. In spite of numberless efforts from government and other developmental agencies women empowerment is still a dream waiting to be reality. Present study was conducted on 240 randomly selected rural women of Bakhariya and Phoolpur villages of Maitha block of district Kanpur Dehat through personal interview method. Results revealed that major constraints towards social empowerment were illiteracy or minimal literacy along with, limited access to mass media. Limited access to credit facilities and gender discrimination were major factors which hampered economical empowerment. Perception of society and Nepotism were the factors that checked political empowerment of rural women. It is suggested to have policy for compulsory education of girls up to intermediate. Gender mainstreaming through agripreneurship could be great aid towards economic empowerment. Trainings and awareness of governmental policies can play crucial role in political empowerment of rural women.
Keywords: Constraints; Control; Empowerment; Intellectual; Knowledge; Resources